Analisis Kromosom Pada Pasangan dengan Keguguran Berulang (Studi Kasus) - Antara, Rizel; Wulandari, Retno Dwi; Narottama, Harya; Setijowati, Eva Diah (Calvaria Medical Journal, 2024)
Background: Miscarriage is the termination of pregnancy before the fetus can live outside the womb. Miscarriage consists of spontaneous miscarriage and induced miscarriage. In Indonesia, the miscarriage rate reaches around 2 million with 10-15% having spontaneous miscarriages. Miscarriages that occur 2 or more times are defined as recurrent pregnancy loss. The incidence of recurrent pregnancy loss is increasing and is estimated to be experienced by around 1-5% of women in productive age. Recurrent pregnancy loss is multifactorial, including uterine anatomical abnormalities, autoimmune factors, endocrine and metabolic disorders, thrombosis, and genetic disorders. Genetic abnormalities include chromosomal abnormalities or mutations in genes. This study aims to determine the chromosomal profile in couples with recurrent miscarriage. Method: This study was a descriptive observational study. Chromosome analysis was performed on a couple with a history of three spontaneous miscarriages. Result: Karyotyping result of the couple were 46,XY and 46,XX. Conclusion: Chromosome analysis in couple with recurrent pregnancy loss in this case study showed no numerical or structural aberration.